Analysis and implementation of the dmaic six sigma method as an effort to control weaving fabric production defects: Industrial textile case study - Nugraha, Evan; Mulyani Sari, Rini; Kurniawan, Asep; Guslan, Darfial (Edelweiss Applied Science and Technology, 2024)
Defective items are those that are produced during the manufacturing process but do not meet the imposed quality standards. These items can be repaired economically if certain costs are covered, which must be less than the post-repair selling value of the product. Semi-finished textiles are produced by the research institute. There are still issues with the production of semi-finished cloth. As a result, the researcher attempted to control and evaluate flaws in the production of semi-finished fabrics by combining the DMAIC approach (Define, Measure, Evaluate, Improve, and Control) with the six-sigma method. A million production operations have a 3.3% Defect Per Million Opportunities (DPMO), or a sigma level value of 2,625 or 133,219 probability of damage, according to the study’s findings. There are two types of production-related damage: non-process and process. After one month of implementing and evaluating improvements, there has been a gradual improvement in all production processes, with the most recent calculation for June 2024 yielding a sigma value of 3.51.